Comment appréhender une littératie en évaluation pour décrire et comprendre le développement des compétences des enseignants ? - Pasquini, Raphaël; Morales Villabona, Fernando (Canadian Journal of Education/Revue canadienne de l’éducation, 2022)
Our research examines the extent to which assessment literacy (AL), which is little developed in the French-speaking research community, appears to be a useful tool for documenting and understanding the development of assessment skills among six secondary school mathematics and French teachers in French-speaking Switzerland. Resulting from a training process promoting exchanges and the creation of summative tests by exploiting specific theoretical contributions, the analysis of our data shows the dynamic development of teachers’ skills, and through that of their AL, using a methodology exploiting the dimensions identified in contemporary literature. More specifically, our results highlight that assessment practices are becoming more consistent, but that grading practices still face obstacles. AL conceptualized in this way is part of a situated, non-technical epistemology. However, it shows the need to further expand the analysis of the negotiations carried out by teachers in their assessment practices to better understand their characteristics.